Prognostic Value of biomarkers hsCRP and NT-proBNP in patients with myocardial infarction: Biomarkers hsCRP and NT-proBNP in myocardial infarction - Kumar, Sanjeev (Student’s Journal of Health Research Africa, 2024)
Background: To evaluate whether serum interleukin-6 (IL-6) and highly sensitive c reactive protein is associated with preferred predictor for risk factor associated to Myocardial Infarction. Aim: The aim of this study was to investigate the Interleukin 6 and high sensitivity C-reactive protein (hsCRP) levels in patients with Myocardial Infarction. Materials and methods: Total numbers of 50 subjects Myocardial Infarction patients were included. hsCRP by immunoturbidimetry method, Interleukin 6 estimation was carried out by sandwich ELISA Method, The inclusion of age group was between 25 to 74 years. Statistical analysis was done by using SPSS, version 21.0. p values were calculated by Quartile ratio, ANOVA unpaired t-test and Kaplan-Meier Curve Method. The p<0.05 was considered statistically significant. All participants had completed questionnaire, physical examination, Present/Past Medical History, and laboratory assessment. Results: The cross-sectional study, Demographic and baseline characteristic of Quartile group of IL-6 and hsCRP are significant (p value= ˂0.001). Lipid profile correlated with quartile ratio association between IL-6 and hsCRP are significant (p value= ˂0.001). IL-6 and hsCRP were each associated participants observed via Kaplan-Meier method with significantly of Quartile 25% vs 40% and Overall comparison of biomarkers (Log rank) chi square test (IL-6= 12.80 p-value= 0.005 vs hsCRP= 7.24 p- value= 0.064). Conclusion: Our study shows that high levels of hsCRP and IL-6 may be used as diagnostic information that provided by the predictable Acute Myocardial Infarction.